What are the changes in basketball shooting pattern and accuracy in National Basketball Association in the past decade? - Wang, Feng; Zheng, Guohua (Frontiers in Psychology, 2022)
The main research question addressed in this study is how the shooting pattern and field-goal accuracy have changed in the NBA league in the past decade. This study analyzes NAB regular seasons data from the 2011-2012 season to the 2020-2021 season. Results reveal an increasing number of field goals per game over the past ten years. In addition, there are drastic changes in the area where basketball players choose to shoot the ball. There is an increasing trend in the percentage of 3-pointer shooting, which has nearly doubled from 22% to 39%. Meanwhile, the percentage of field goals within the range of 16-24 ft has decreased from 20% to 10%. For all shooting zones, field-goal accuracy has shown an increasing trend except for the 3-pointer shooting. Sixteen equal segments, each with three minutes, were analyzed to examine the shooting pattern in different segments of the game. The second and fourth 3-minutes within each quarter have the highest number of field goals. The first quarter has a higher shooting accuracy than the rest three quarters. In addition, results reveal that the last 3-minute in each quarter has the lowest shooting accuracy. Reasons for the patterns of field goals in different segments are discussed from game rule changes, the fatigue effects, and game strategy perspectives. Mann-Kendall trend tests were employed to examine if changes are statistically significant over the years. This study offers new insights into the changes in basketball shooting patterns and accuracy in NBA games in the past decade.